Sunday

January 25, 2015

January 25, 2015

Posted by **G** on Tuesday, January 18, 2011 at 10:53pm.

- algebra -
**Aman**, Wednesday, January 19, 2011 at 2:01am9x+6y=3 (1)

3x-7y=-26 (2)

using substitution method in (1) we get

9x+6y=3

dividing by 3 both side we get

3x+2y=1

taking 2y to the other side (here 2y in + so when we change its side it will be -)

3x=1-2y

(here 3 is multiply with x so when it goes other side sign will change in divide)

x=(1-2y)/3 (3)

3x-7y=-26 (2)

putting the value of x in (2) from (3)

3*(1-2y)/3-7y=-26

(3 will cancel by 3)

1-2y-7y=-26

1-9y=-26

taking constant no. Same side

-9y=-26-1

-9y=-27

(both sides minus sign will cancel by each other)

9y=27

y=27/9

y=3

putting the value of y in (3)

x=(1-3*2)/3

x=(1-6)/3

x=-5/3

(u can check ur ans by putting the value of 'x' and 'y' in (1) and (2))

**Answer this Question**

**Related Questions**

Algebra 1 - bobpursey, In this problem you helped me with earlier: Solve using ...

Algebra - Solving system of linear equations by using the apropiate method name ...

algebra - o Systems of equations can be solved by graphing or by using ...

Algebra - Systems of equations can be solved by graphing or by using ...

Algerbra 1 substitution method - im really confused about this question: 2x-3y=...

algebra - use the Substitution Method. Please give it a try. y = 3x + 4 5x + 3y...

Algebra - Systems of equations can be solved by graphing or by using ...

Algebra 2 - 2x-y+=-9 3x-8y=-7 using the substitution method.

algebra - 9x+6y=3 and 3x-7y=-26 using the substitution method

algebra - 9x+6y=3 and 3x-7y=-26 using the substitution method